A meta-analytic review of social cognitive function following stroke. (July 2019) - Adams, Alexandra G.; Schweitzer, Daniel; Molenberghs, Pascal; Henry, Julie D.
Highlights: Large deficits in social perception and social behaviour are evident post-stroke. Following stroke, difficulties with theory of mind are of a moderate magnitude. Problems with affective empathy are moderate in magnitude but not significant. Social cognitive deficits generalise across stroke laterality and task features. Social cognitive measures should be routinely included in post-stroke assessment. Abstract: Although it is now widely recognised that social cognitive difficulties are often evident following stroke, important questions remain about the nature and magnitude of these difficulties, as well as the factors that determine the magnitude of this impairment. A meta-analysis of 58 datasets involving 2567 participants (937 with stroke, 1630 non-clinical controls) was therefore conducted. The results indicated that three of the four core domains of social cognitive function were significantly disrupted in people with stroke. Specifically, while the effect size for affective empathy failed to attain significance ( r = −.33), moderate to large deficits were identified for theory of mind ( r = −.44), social perception ( r = −.55), and social behaviour ( r = −.53). These deficits were robust across both left and right lateralized lesions, across social cognitive assessments that differed in their broader cognitive demands, as well as in tasks that varied in their modality of presentation. These data are discussed in the context of broader neuropsychological models of social cognitive function.